Using Information and Communications Technology to Reduce Poverty in Rural India - Cecchini, Simone; Prennushi, Giovanna (World Bank, Washington, DC, 2012)
The note focuses on experiences in rural India, showing that information and communications technology (ICT) can enhance poor people's opportunities, by improving access to markets, as well as health care. Furthermore, it can empower them by expanding their use of government services, including increased security, and widened access to micro-finance. A revision follows on the computerized milk collection centers in Gujarat which ensures fair prices for small farmers, and, on enabling auxiliary nurse midwifes' services in Andhra Pradesh, by freeing time to deliver health care to poor people. Also reviewed is the case of Gyandoot - a government-owned computer network - making government accessible to villagers in the poor, drought-prone Dhar district in Madhya Pradesh, where immediate, and transparent access to local government data, and documentation is provided. A micro-finance institution in the Medak district of Andhra Pradesh, facilitates Smart Cards, that hold information on clients credit histories, lowering transaction costs, reducing errors, as well as fraud. However, designing interventions that reach the poor is successful, provided grassroots intermediation is taken into account, as well as local ownership, local languages, training, and awareness.